The Influence of Group and Individual Physiotherapy on Balance of Children with Impaired Language and Communication - Olga Kuznecova; Rasa Šakalienė (Lithuanian Sports University, 2020)
Communication disorder is a relatively constant deviation from the agreed standards of speech, language and communication. It is observed that communication disorders such as alalia, dysarthria, often go with disorders of gross and small motor functions, movements which lack of rhythm, impaired balance. The aim of the study was to test the efficiency of group and individual physiotherapy on balance for children with impaired language and communication. The study included 75 children aged 3-6 years. The target was divided into two groups: the exploratory group consisted of children who had impaired language and communication and the disorder is not due to other disorders; the control group consisted of children of the same age whose development was normal and they did not have language or other problems. The tested group children were divided into two groups at random: the first and the second. The first group underwent individual physiotherapy, while the second one participated in group physiotherapy. Procedures of physiotherapy lasted for 2 months, 2 times per week. Their duration was 30 minutes. The physiotherapy program consisted of various balance exercises standing or moving, using smaller base of support or soft balance platforms. Various games were also used during the group physiotherapy sessions. Conclusions. Balance of the three-six year old children with language and communication disorders was significantly worse than that of their healthy peers. Children balance depends on the degree of language impairment: children with an average degree of undeveloped language disorder demonstrated balance significantly better than that of children with significant language undevelopment. Balance of pre-school children with language and communication disorders statistically significantly improved in both individual and group physiotherapy procedures. Balance of children with language and communication disorders who had individual therapy improved a little more than those in the group therapy but the difference was not statistically significant. Keyword: language and communication disorders, physical therapy, postural control.